Monitoring the sentiment of cannabis‐related tweets in the lead up to New Zealand's cannabis referendum. (6th October 2020) - Riordan, Benjamin C.; Raubenheimer, Jacques; Ward, Rose Marie; Merrill, Jennifer E.; Winter, Taylor; Scarf, Damian
Abstract: Introduction and Aims: In October 2020, New Zealanders will vote on whether cannabis should be legalised for recreational use. With this in mind, the aim of the present study is to gauge the views and opinions of the New Zealand population on cannabis via tweets. To achieve this, we conducted a sentiment analysis of all historic cannabis‐related tweets and referendum‐specific tweets written in New Zealand. Design and Methods: We used a Twitter‐sponsored commercial platform to access all historic cannabis‐related tweets written in New Zealand and used search terms to remove non‐cannabis‐related terms. Next, we used the platform's machine learning function to code the sentiment of tweets (i.e. positive/pro‐cannabis, negative/anti‐cannabis or neutral). Results: Between July 2009 and August 2020, 304 760 cannabis‐related tweets were written in New Zealand. Overall, the tweets were predominantly positive (62.0%) and there was a higher proportion of positive tweets written in 2020 (65.3%) compared to negative or neutral tweets. Similarly, for referendum‐specific tweets, the 2020 data reveal a generally positive view of cannabis (53.5%). Discussion and Conclusions: Both cannabis‐related, and referendum‐specific tweets, suggest that Twitter users in New Zealand have a generally positive view of cannabis. Given the nature of Twitter, the current method will allow us to study whether views toward cannabis change as the referendum nears and capture any late swings in pro‐ or anti‐cannabis sentiment (abcd‐lab.shinyapps.io/cannabis_sentiment/).